Epistemological Obstacle on the Material of Circumference and Area of Plane in Grades 4 and 5 of Elementary School - Fauzi, Irfan; Suryadi, Didi (International Conference on Elementary Education, 2020)
Geometry is one of the subject matter taught from elementary to higher education, one of the material taught in geometry in elementary school is circumference and area of plane material. This study aims to analyze of epistemological obstacle of fourth and fifth grade students of SD Negeri Asmi 033 Bandung City in answering circumference and area of plane question. This study used an exploratory study in the form of a written description test on the circumference and area of plane material given to fourth and fifth grade students of SD Negeri Asmi 033 Bandung City. The results of the analysis show that there are still many students who experience learning obstacle related to epistemological. This research is expected to be taken into consideration by teachers in seeing students' learning obstacles to be used as material in making didactic designs on the Material of Circumference and Area of Plane in Grades 4